Physicochemical and Organoleptic Characteristics of Ginger Jelly Candy using Secang (Caesalpinia sappan L) as Natural Dye - Jesica Maria Kumalasari; Nanik Suhartatik; Vivi Nuraini (Fakultas Sains dan Teknologi Unisri, 2026)
Jelly candy is a food product that has a chewy texture. One type of jelly candy that is popular with the public is ginger candy, but some people don't like ginger candy because ginger candy has a very spicy taste and low vitamin C content. Based on these problems, it is necessary to substitute it with lemongrass extract to increase the vitamin C content and minimize the spicy taste of the red ginger jelly candy. There are candies on the market that still use synthetic food coloring which can be harmful to health. This research aims to produce jelly candy that has high antioxidant activity and color that is preferred by consumers. This study used a Completely Randomized Design (CRD) with the first factor being the ratio of ginger extract and lemon grass extract (27,5 ml : 12,5 ml), (15 ml : 15 ml) and (12,5 ml : 27,5 ml). The second factor was the concentration of sappan extract in 250 ml of 0.06 % water; 0.08 %; 0.1 %. The results showed that the formulation of 27.5 ml ginger extract and 12.5 ml lemon grass with 0.06 % sappan extract had high antioxidant activity. This formulation has an antioxidant activity value of 38.36 %. The jelly candy formulation that produced the best color was found in the formulation of 27.5 ml of ginger extract and 12.5 ml of ginger extract with 0.06 % sappan extract with a score of 3.94 (brownish yellow). Jelly candy with lemongrass and sappan substitutes can increase antioxidant activity and give a good color to the product